The Role of the Agulhas System in Regional and Global Climate: AGUChapman Conference: The Agulhas System and Its Role in Changing Ocean Circulation, Climate, and Marine Ecosystems; Stellenbosch, South Africa, 8–12 October 2012. (6th March 2013) - de Ruijter, Wilhelmus P. M.; Beal, Lisa; Biastoch, Arne; Zahn, Rainer
Abstract : The AGU Chapman Conference on the Agulhas system was the first held on the African continent. There was a feeling of excitement among participants about the great diversity of ongoing research related to the Agulhas Current system, including its role in global and regional climate, its possible influence on human origins in southern Africa, its link to the Madagascar phytoplankton bloom, and its influence on South Atlantic hurricane development (Catarina) through warming related to Agulhas leakage over the past decades.